1993
DOI: 10.1093/cvr/27.7.1155
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors and angiogenesis

Abstract: The list of growth factors with angiogenic potential is growing. It is not clear why so many factors with angiogenic potential exist, although Folkman postulated that this apparent redundancy is indicative of the essential nature of the angiogenic response. Additionally, these factors or their close relatives have other biological activities, including developmental morphogenesis, tumourigenesis, regeneration of injured tissue, and immunosignalling. Recent advances in the understanding of these factors include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…In addition, they have been considered to be part of mechanisms responsible for angiogenic, antiapoptotic, and mitogenic effects after cell transplantation [51,52]. Similar to previous studies, our current study showed that VEGF, which is best known as a key mitogen for ECs [53,54], could promote the proliferation of ECs in vitro. Interestingly, IGF-1, which had a proangiogenic effect [55], increased noticeably in BMMCs-CM, and it was found that IGF-1 was also related to cell proliferation of ECs in vitro.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, they have been considered to be part of mechanisms responsible for angiogenic, antiapoptotic, and mitogenic effects after cell transplantation [51,52]. Similar to previous studies, our current study showed that VEGF, which is best known as a key mitogen for ECs [53,54], could promote the proliferation of ECs in vitro. Interestingly, IGF-1, which had a proangiogenic effect [55], increased noticeably in BMMCs-CM, and it was found that IGF-1 was also related to cell proliferation of ECs in vitro.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous angiogenic factors have been identified (3,61). Which growth factor(s) are responsible for induction of angiogenesis by Nf1-deficient Schwann cells has not been addressed in this study.…”
Section: Discussionmentioning
confidence: 98%
“…VEGF, also known as vascular permeability factor, is expressed in response to hypoxia and other stimuli by a variety of differentiated cells (1, 2, 6 -14). VEGF expression has also been found in numerous human and rodent transformed cells (3,4,(15)(16)(17)(18)(19). VEGF is encoded by a single gene, but it exists in four isoforms of 121, 165, 189, and 206 amino acids due to alternative mRNA splicing (20,21).…”
Section: Vegfmentioning
confidence: 99%
“…In addition to VEGF, PLGF has also been demonstrated to bind FLT-1 with high affinity, but not to KDR/Flk-1 (34,35). VEGF is a potent endothelial cell mitogen in vitro, while PLGF is 3 orders of magnitude less potent at inducing endothelial cell proliferation (4,(15)(16)(17)(18). However, PLGF can significantly potentiate the in vitro and in vivo activity of low concentrations of VEGF (34).…”
mentioning
confidence: 99%